Spinal Versus General Anesthesia for Laparoscopic Cholecystectomy (TAJ: Journal of Teachers Association, 2018)
Laparascopic Cholecystectomy under regional anesthesia alone has been reported only with severe chronic obstructive airway disease1,2. In a randomised trial, epidural with general anesthesia have been found to be more effective in lessening postoperative pain compare with general anesthesia alone3. Regional anesthesia has been successfully used for laparascopic cholecystectomy in patient. Hamad and Ibrahim El-Khatter4 used spinal anesthesia for laparoscopic for the first time. We performing Laparascopic Cholecystectomy with carbondioxide pneumoperitoneum under spinal anesthesia alone of healthy patients with symptomatic gall stone disease5. We design a control randomized trial to compare spinal anesthesthesia with the Gold standard general anesthesia for elective Laparascopic Cholecystectomy in healty patients.TAJ 2012; 25: 55-58